Micronized cellular adipose matrix as a therapeutic injectable for diabetic ulcer. (September 2015) - Feng, Jingwei; Doi, Kentaro; Kuno, Shinichiro; Mineda, Kazuhide; Kato, Harunosuke; Kinoshita, Kahori; Kanayama, Koji; Mashiko, Takanobu; Yoshimura, Kotaro
Background: Despite the clinical potential of adipose-derived stem/stromal cells (ASCs), there are some clinical difficulties due to the regulation of cell therapies.Materials & methods: Micronized cellular adipose matrix (MCAM) injectable was prepared through selective extraction of connective tissue fractions in fat tissue only through mechanical minimal manipulation procedures.Results: It retained some capillaries and ASCs, but most adipocytes were removed. The presence of viable ASCs, vascular endothelial cells was confirmed and ASCs of MCAM kept intact mesenchymal differentiation capacity. In diabetic mice, skin wounds treated with MCAM showed significantly accelerated healing compared with phosphate-buffered saline-treated ones.Conclusion: The proven potential of MCAM to accelerate healing in ischemic diabetic ulcers may offer a simple, safe and minimally invasive means for tissue repair and revitalization.